Satsa på leken! : en studie om skolgårdens betydelse för barns lek och utveckling - Andersson, Åsa (SLU/Dept. of Urban and Rural Development, 2010)
The intention of this final thesis is to examine how to create a schoolyard that inspires children at the age of 6 – 12 years to play and give them possibility to develop. To get a lot of knowledge in this subject, I have combined studies of literature with practical studies at Hosjöskolan in Falun. During my practical studies I have done interviews, walks in the area with the children and visited other schoolyards. I have based a design proposal for the schoolyard of Hosjöskolan on these studies. Then I have checked the design proposal against the literature.